Charity and Progress - Cummings, Edward (Quarterly Journal of Economics, 1897)
Charity and Progress* Edward Cummings Edward Cummings Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 12, Issue 1, October 1897, Pages 27–41, https://doi.org/10.2307/1882307 Published: 01 October 1897